2022
DOI: 10.3390/insects13100955
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory Evaluation of Storage Bags for Infestations in Wheat Caused by Rhyzopertha dominica F. (Coleoptera: Bostrichidae) and Trogoderma granarium Everts (Coleoptera: Dermestidae) and Their Control Using Phosphine Fumigation

Abstract: Bag storage of wheat is common in Asian countries, and common types of such bags include jute bags, woven plastic bags, and hermetic plastic bags. In order to assess infestation by two serious pests, namely Rhyzopertha dominica (Coleoptera: Bostrichidae) and Trogoderma granarium (Coleoptera: Dermestidae) in these bags, two experiments were performed. In the first experiment, three popular wheat varieties, namely Akbar, Dilkash, and Bakhar star were filled in above-mentioned miniature-size bags which were then … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…dominica to benefit from it in carrying out all the experiments included in this study The plastic jars were kept in the laboratory incubator under 30 ± 2 °C and 65 ± 2% RH. Daily data on both temperature and relative humidity are recorded using a device a thermo-hygrometer [24]. After two weeks, the adults were removed to obtain individuals of the new generation, and the insect cultures were renewed after each generation and as needed [25].…”
Section: Insect Collections and Rearingmentioning
confidence: 99%
“…dominica to benefit from it in carrying out all the experiments included in this study The plastic jars were kept in the laboratory incubator under 30 ± 2 °C and 65 ± 2% RH. Daily data on both temperature and relative humidity are recorded using a device a thermo-hygrometer [24]. After two weeks, the adults were removed to obtain individuals of the new generation, and the insect cultures were renewed after each generation and as needed [25].…”
Section: Insect Collections and Rearingmentioning
confidence: 99%
“…Foodstuff packaging derived from plastics like polypropylene with a thickness of 0.04 mm was found to be resistant to insect penetrations or invasions of a major stored grain borer, Rhyzopertha dominica ( Hassan et al, 2016 ). Previous research done by the study researchers evaluating the susceptibility of flexible plastic foodstuff packaging found that major stored grain insects were able to tear plastic packaging and consume or remove some of the food inside, leading to weight loss in the packaged foodstuffs ( Qasim et al, 2013 ; Hassan et al, 2014 ; Hassan et al, 2016 ; Yar et al, 2017 ; Akram et al, 2018 ; Hussain et al, 2019 ; Waheed et al, 2022 ). However, little or no research is currently available on the susceptibility of commonly-used flexible plastic foodstuff packaging against household ants.…”
Section: Introductionmentioning
confidence: 99%
“…Conf. Series: Earth and Environmental Science 1230 (2023) 012096 IOP Publishing doi:10.1088/1755-1315/1230/1/012096 4categorized as a penetrator of packaging that could penetrate the packaging by creating holes as an entranceway through the packaging[19,20].…”
mentioning
confidence: 99%